The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1002/(sici)1097-4571(199404)45:3<149::aid-asi5>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

User-defined relevance criteria: An exploratory study

Abstract: The objective of this study was to describe the criteria mentioned by users evaluating the information within documents as it related to the users' information need situations. Data were collected by asking users in an academic environment to evaiu-ate representations and the full text of documents that had been retrieved specifically for each user's information need situation. Users were asked to mark the portions of the document representations or of the full text of documents that indicated to the users whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
307
0
13

Year Published

1994
1994
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 354 publications
(332 citation statements)
references
References 26 publications
12
307
0
13
Order By: Relevance
“…Research into the concept of relevance has indicated that topicality plays a significant role in the determination of relevance, although it does not automatically result in relevance for users (Barry, 1994).…”
Section: Limitationsmentioning
confidence: 91%
“…Research into the concept of relevance has indicated that topicality plays a significant role in the determination of relevance, although it does not automatically result in relevance for users (Barry, 1994).…”
Section: Limitationsmentioning
confidence: 91%
“…), publishing date (e.g., year), and its text. These attributes can contain specific words, i.e., terms that can be recognized by the information seeker as relevant and trigger the formulation of refined search queries (Barry, 1994;Anderson, 2006).…”
Section: Information Seekingmentioning
confidence: 99%
“…They found that typicality, emotion and aesthetic appearance were the three most important criteria, applied across all three tasks, where typicality was deemed the most important criterion for all three tasks (according to the authors, typicality is a criterion that can exhibit universal representation of an object in a photo). Lancaster (1979); Barry (1994); Barry and Schamber (1998);Mizzaro (1997); Choi and Rasmussen (2002) and Tang and Solomon (1998) reported that the end-users of IR systems decided the relevance of retrieved documents based upon their particular information needs.…”
Section: Image Relevance Studiesmentioning
confidence: 99%